2007
DOI: 10.1182/asheducation-2007.1.332
|View full text |Cite
|
Sign up to set email alerts
|

Management of Infectious Complications in Patients with Chronic Lymphocytic Leukemia

Abstract: Infections remain a major cause of morbidity and mortality in patients with chronic lymphocytic leukemia (CLL). The pathogenesis of these complications is related to immune defects inherent to the primary disease as well as to therapy-related immunosuppression. The spectrum of infections seen has evolved with the therapeutic use of purine analogs, which induce specific cellular immune defects, as well as the monoclonal antibodies alemtuzumab and rituximab. Although bacterial infections are most common, fungal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 54 publications
2
72
0
9
Order By: Relevance
“…20 The risk of infection increases over time, especially in heavily pretreated patients with active disease, and is usually the cause of death in advanced CLL.…”
Section: Infectious Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The risk of infection increases over time, especially in heavily pretreated patients with active disease, and is usually the cause of death in advanced CLL.…”
Section: Infectious Complicationsmentioning
confidence: 99%
“…Common organisms include S pneumonia, S aureus, H influenzae. 20 Recurrent infections are common and may lead over time to chronic sinusitis and bronchiectasis in susceptible individuals. Herpes virus reactivation is relatively common, with H zoster being most frequent.…”
Section: Infectious Complicationsmentioning
confidence: 99%
“…Several studies indicated that .50% of patients with CLL suffer from pathogen colonization, causing the death of 70% of these patients (4)(5)(6)(7)(8)(9)(10). Other studies reported that 80% of patients with CLL suffer from infections (11).…”
mentioning
confidence: 99%
“…Disseminated candidiasis and aspergillosis are well recognized offenders. Concurrent treatment with steroids increases the likelihood of pneumocystis infections (93). Viral infections are common, especially varicella zoster virus (VZV) infection, which may be complicated by a high incidence of post-herpetic neuralgia.…”
Section: Purine and Pyrimidine Analoguesmentioning
confidence: 99%